FACTORS AFFECTING THE ROLE OF NURSES IN MEDICATION SAFETY A LITERATURE REVIEW - Fanda Lalujan; Lisa Musharyanti (Jurnal Keperawatan Respati Yogyakarta, 2021)
Mistakes during medical treatments are a rising concern in patient safety. Nurses are critical in ensuring the safe administration of drugs to patients influenced by various factors. This literature review aims to identify factors influencing nurses in medication safety. The pieces of literature were sourced from the PubMed Proquest Science Direct and Willey Library electronic databases with search terms of risk factor or related factor nurse or nurse role medication error drug safety drug administration. The review process resulted in twenty three original articles meeting the inclusion criteria. The review shows five main factors influencing a nurses role in medication safety which are organization & management training programs; career paths; medication error reporting systems staffing information systems working environment additional routines official shifts number of service days interruptions during action workloads work learning culture team leadership style oral and written communication nurses personal and work history age length of work experience education knowledge and skills/competence motivation and attitude nurse awareness and task availability & use of protocol. Keywords: Nurses Role; Medication Errors; Patient Safety; Medication System